Towards a Transboundary Haze-Free ASEAN by 2020: Some Immediate Actions - Raman Letchumanan (2015)
The efforts towards a transboundary haze-free ASEAN by 2020 would require immediate actions on the following priority areas to be able to contain uncontrolled outbreak of fires in the near term.